Локальна специфіка традиційних звичаїв та обрядів великоднього циклу на Волинському Поліссі (за польовими матеріалами Державного наукового центру захисту культурної спадщини від техногенних катастроф, зібраними в Камінь-Каширському р-ні Волинської обл.) - Kovalchuk, Nadiya; Ковальчук, Надія (Східноєвропейський національний університет ім. Лесі Українки, 2013)
На основі виділення в обрядових явищах притаманних їм структурних елементів (акціональних, вербаль-них, предметних, темпоральних, персональних) і порівняльного аналізу їх варіативності визначено західно-поліські варіанти звичаїв та обрядів великоднього циклу на прикладі Камінь-Каширського району Волинської області.The article highlights and analyzes specific peculiarities of traditional consuetudes and rituals of the Volynske Polissya' paschal calendar cycle using the example of Kamin-Kashyrskyi district of Volyn region. On the basis of separation of inherent structural elements (functional, verbal, substantive, temporal, personal) in ritual phenomena and comparative analysis of their variability, the variants of the paschal cycle consuetudes and rituals from Western Polissia were defined. Such variants are being identified in ceremonialisms dedicated to «Zapusty», «Seredohresnyi Tyzhden», «Easter of Dead», «Pereplavna Sereda», in Polish festival «Bozhe Tilo» distribution. These variants may be observed in «volochebni», memorial and mermaid traditions. It is found out that the festivals of «Vlas» and «Deviatuha» are not celebrated within the explored territory.
Local Specificity of Traditional Consuetudes and Rituals of the Paschal Cycle Within the Territory of Volynske Polissya (Based on the Obtained in Kamin-Kashyrskyi District, Volyn Region Field Materials by the State Scientific Center for Cultural Heritage Protection From Technogenic Catastrophes).
Keywords: календарний обряд; звичай; традиція; великодній цикл; Волинське Полісся; calendar ritual; consuetude; tradition; paschal cycle; Volynske Polissya